Odpowiedzi

2010-03-02T19:49:15+01:00
A) -3x = 2x - 10
-3x-2x=10
-5x=10/:5
x=2

b) -(2x-2) = 4
-2x+2=4
-2x=4-2
-2x=4/:-2
x=-2

c) 2(x+1) = x
2x-2=x
2x-x=2
x=2

d) -(4=x) = 2 (3-x)
-4-x=-6-2x
-x+2x=-6+4
x=2

e) (x-7) - 2 (3x=5) = 3
x-7-6x-10=3
x-6x=3+7+10
-5x=20/:-5
x=-4
2010-03-02T20:09:42+01:00
A) -3x = 2x - 10
5x = 10
x = 2

b) -(2x-2) = 4
-2x+2 = 4
2x = -2
x = -1

c)2(x+1) = x
2x+2 = x
x = -2

d) -(4+x) = 2 (3-x)
-4-x = 6-2x
x = 10

e)(x-7) - 2 (3x+5) = 3
x-7-6x-10 =3
-5x-17 = 3
5x = -20
x = -4

:)